The impact of geographical discoveries on European colonial expansion (Journal of Imam Al-Kadhim College, 2025)
Abstract:      The geographic exploration movement was one of the most important aspects of the European Renaissance. This movement was active from the second half of the fifteenth century AD and reached its peak in the sixteenth century AD. Several motivations and factors contributed to its development and influenced its outcomes. Perhaps the most prominent outcome of the geographic exploration movement was the launch of European colonialism in the discovered regions and the emergence of competition among countries over spheres of influence based on the economic, political, religious, and other interests they achieved. This is the subject of our research, entitled "The Impact of Geographical Exploration on European Colonial Expansion." We reached several conclusions, including the attempts of a number of colonial powers to encourage their citizens to settle in the colonies and establish a form of political administration in their territories. Several factors also underpinned the geographic exploration movement, most notably the economic motive and the search for spices and gold, as well as the religious factor. Furthermore, the European colonial powers were determined to find new lands to solve their social and political problems.
Keywords: discoveries - colonization - Renaissance – Europe